If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(7X + -9) = 42 Reorder the terms: 6(-9 + 7X) = 42 (-9 * 6 + 7X * 6) = 42 (-54 + 42X) = 42 Solving -54 + 42X = 42 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + 42X = 42 + 54 Combine like terms: -54 + 54 = 0 0 + 42X = 42 + 54 42X = 42 + 54 Combine like terms: 42 + 54 = 96 42X = 96 Divide each side by '42'. X = 2.285714286 Simplifying X = 2.285714286
| c+-8=-8 | | c+6=5 | | 10x-16=2x | | 2-(4X-17)=6(X-2) | | 5y^2+3y-10=0 | | -6+r=-16 | | 4+t=4 | | a+15=20 | | -24=8t(1-2t) | | (-0.4x^2-0.1x+1)=0 | | x+2*6x=3x+15 | | 10=30x^2 | | -15x+35=20 | | 25+x=-9 | | 54=-4x | | -13=x+17 | | hongki+2x=0 | | a-5=-4 | | x^2+2hx=x-h^2 | | 27(x^2-4x+4)-12=0 | | 4h^2+4x^3+4h^2x=0 | | 5x+18y-14z=12 | | 9267910643x+790x-7780=387 | | 27x^2+96=0 | | 2x+5=5x+9 | | 173x+928x=41*x | | 173x+928x=41 | | -24y^2=9y | | X-0.7=8.47 | | 4x^3-12x^2+2x+18=0 | | 30r^2=-15r | | 4x-29=-21+6x |